Setting up and managing a small hotel - Lim, Lino Ed (Anvil, 2008)
"Setting Up and Managing a Small Hotel provides everything the would-be hotelier needs to know--from building the edifice to setting up the management and the organizational structures, defining the duties and responsibilities of each employee, and setting out the policies and procedures for each department. The book also gives previews of how key departments work around the clock, sample forms used in daily operations and tips to achieve guest satisfaction. This is a valuable textbook for students and a must-have guide for people looking to build a career in the hospitality industry.--Joseph H. Durano"--Back cover.